Phylogenetic analysis of rabies virus in mammals reported in Colombia between 1994 and 2008 (2014)
Rabies is a viral zoonosis distributed worldwide that affects the central nervous system. Epidemiologically, due to the form of transmission rabies has been classified into two categories: urban form, associated with canine and feline, and sylvatic, involving vampire bats. In Colombia, the first rabies virus was isolated in 1968 from the vampire bat (Desmoncus rotundus), and since then the population has been historicall affected by urban and jungle outbreaks. The objective of this study was to analyze 19 partial sequences of nucleocapsid protein N of rabies virus reported in Colombia, and deposited in GenBank between 1994 and 2008, to establish their phylogenetic relationships. The phylogeny showed four monophyletic groups. Epidemiologically, two forms of transmission of the virus (urban and sylvatic cycle) are present, with implications for public health. Therefore, it is necessary to implement prevention and control measures to reduce the impact of the zoonosis on the human population.